The Admissibility of Statements Provided by an Accused Person in the Russian Criminal Procedure - KOSTENKO, Roman; YURIEV, Georgii (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
This article substantiates that compliance with the requirement of admissible evidence acquires special significance for a criminal proceedings, which is proved by the analysis of various sources, including the current edition of the Criminal Procedure Code of the Russian Federation. Therefore, the article aims to determine the nature of admissible statements of the accused in the Russian criminal procedure as one of the most important types of legal evidence. The authors of the article have obtained crucial results for the study of criminal proceedings, defined the basic requirements that should be met by admissible statements of an accused person, analyzed rules for admitting statements of the accused, performed their general characterization and formulated the main provisions defining the essence of statements provided by the accused in criminal proceedings. The main conclusion reached in this article is that the admissibility of statements provided by the accused should comply with the following basic rules: (1) the rule of appropriate subjects authorized by virtue of the existing Criminal Procedure Code of the Russian Federation to carry out procedural actions for collecting (obtaining, recording) evidence; (2) the rule of proper information sources on the facts provided for by the current Criminal Procedure Code; (3) the rule of proper proceedings stipulated by the current Criminal Procedure Code of the Russian Federation for collecting (receiving, recording) evidence; (4) the rule of the proper procedure provided for by the current Criminal Procedure Code for collecting (receiving, recording) evidence from the viewpoint of its proper obtaining is considered as the need to comply with requirements of the Criminal Procedure Code.